2000
DOI: 10.1111/j.1744-7348.2000.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of non‐tuber bearing Solanaceae for resistance to and induction of juvenile hatch of potato cyst nematodes and their potential for trap cropping

Abstract: Ninety accessions of non-tuber bearing Solanaceae were screened for (i) resistance to and (ii) stimulatory effect on juvenile hatch of potato cyst nematodes, and (iii) their growth under temperate climatic conditions. All plant species belonging to the genus Solanum tested induced hatching but this effect was most pronounced for plant species of the Solanum nigrum complex. Hatching ofjuveniles was hardly or not stimulated by other plant genera of the Solanaceae. Solanum sisymbrilfolium combined a high hatching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 17 publications
4
44
1
Order By: Relevance
“…Domino may be included in control programs against M. javanica as the root exudates induced hatching of J2. Similar results were obtained by Scholte (2000b) and Timmermans (2005) with exudates of S. sisymbriifolium in the emergence of J2 of Globodera spp. The cv.…”
Section: Hatching Testssupporting
confidence: 91%
“…Domino may be included in control programs against M. javanica as the root exudates induced hatching of J2. Similar results were obtained by Scholte (2000b) and Timmermans (2005) with exudates of S. sisymbriifolium in the emergence of J2 of Globodera spp. The cv.…”
Section: Hatching Testssupporting
confidence: 91%
“…For the beet cyst nematode (Heterodera schachtii), such trap crops have been successfully developed and have been used practically (Hafez and Sundararaj, 1998;Koch et al, 1998;Koch and Gray, 1997;Krall et al, 2000). Scholte (2000a) screened Solanum nigrum and S. sisymbriifolium from a lot of solanaceous plants as potential trap crops for potato cyst nematode. These plants stimulated hatching of potato cyst nematode eggs, but they are completely or highly resistant to the nematode.…”
mentioning
confidence: 99%
“…Scholte (2000) showed that G. pallida could be controlled using a trap crop system based on potato plants that were destroyed after an 8-week growing period with the systemic herbicide glyphosate. Also, Turner et al (2006) showed G. pallida field populations could be reduced using selected wild Solanaceae potato clones.…”
Section: Discussionmentioning
confidence: 99%